Distribution and growth in France and Germany - single equation estimations and model simulations based on the Bhaduri/Marglin-model - Eckhard Hein; Lena Vogel (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2007)
The authors analyse the relationship between functional income distribution and economic growth in France and Germany from 1960 until 2005. The analysis is based on a demand-driven distribution and growth model for an open economy inspired by Bhaduri/Marglin (1990), which allows for profit- or wage-led growth. First, the authors apply a single equation approach, estimating the effects of redistribution on the demand aggregates and summing up these effects in order to obtain the total effect of redistribution on GDP growth. Since interactions between the demand aggregates are omitted from this approach, the authors also apply a simulation approach taking into account these interactions. In the single equations approach the authors find that growth in France and in Germany was wage-led. This qualitative result is confirmed by the simulation approach, but the quantitative effects differ somewhat. Whereas in the single equation approach the wage-led nature of the demand regime in Germany seems to be more pronounced than in France, in the simulation approach the effects in the two countries seem to converge.
urn:nbn:de:101:1-20080814238
Keywords: E12; E21; E22; E23; E25; 330; Distribution; growth; demand-led accumulation regimes; Funktionelle Einkommensverteilung; Wirtschaftswachstum; Frankreich; Deutschland